2019
DOI: 10.1016/j.nicl.2019.101958
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of parietal hyperactivation in individuals with mild cognitive impairment who progressed to dementia: A longitudinal fMRI study

Abstract: Hyperactivation, which is defined as a higher level of activation in patients compared to cognitively unimpaired older adults (controls; CTL), might represent an early signature of Alzheimer's Disease (AD). The goal of this study was to assess the presence and location of hyperactivation in individuals with mild cognitive impairment (MCI) who were later diagnosed with dementia, examine how hyperactivation changes longitudinally, and whether it is related to time before dementia. Forty participants, 26 with MCI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 78 publications
(117 reference statements)
2
27
0
Order By: Relevance
“…Next, we investigated if the BEM indices derived from measuring the high-energy phosphates and membrane phospholipid metabolites at 7T showed a correspondence with cognitive performance (BEM-Cognitive correlates). Overall, we hypothesized an inverse relationship across BEM indicesenergy reserve, energy consumption, and metabolic statealong with regulatory co-factors pH and Mg 2+ and membrane phospholipid index with cognitive performance supported by previous work from Ashraf et al (2015), Croteau et al (2018), andCorriveau-Lecavalier et al (2019). Our results support our assumptions of an inverse relationship in aMCI with the exception of Mg 2+ and the membrane phospholipid index, which were positively associated with visuospatial domain and attention, respectively.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Next, we investigated if the BEM indices derived from measuring the high-energy phosphates and membrane phospholipid metabolites at 7T showed a correspondence with cognitive performance (BEM-Cognitive correlates). Overall, we hypothesized an inverse relationship across BEM indicesenergy reserve, energy consumption, and metabolic statealong with regulatory co-factors pH and Mg 2+ and membrane phospholipid index with cognitive performance supported by previous work from Ashraf et al (2015), Croteau et al (2018), andCorriveau-Lecavalier et al (2019). Our results support our assumptions of an inverse relationship in aMCI with the exception of Mg 2+ and the membrane phospholipid index, which were positively associated with visuospatial domain and attention, respectively.…”
Section: Discussionsupporting
confidence: 88%
“… Ashraf’s et al (2015) research supported increased metabolism (hypermetabolism) in the occipital cortex in MCI compared to healthy controls using 18 FDG PET. Similarly, a longitudinal study in 26 MCI by Corriveau-Lecavalier et al (2019) found that parietal lobe hyperactivation in 13 MCI was an early indicator in individuals who progressed to dementia. In MCI, based on Ashraf’s and Corriveau’s findings in the parietal and occipital lobes separately, we hypothesized that there may be compensatory hyperactivation, which may be a proxy of higher cerebral blood flow and energy metabolism during the early phases of biological changes, which may be associated with worsening of cognitive performance.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In the presence of mild neurodegeneration, a high level of activation may be consistent with a higher risk of progression in cognitively intact older adults complaining about their memory. Furthermore, while some studies investigated fMRI dynamics in relation to amyloid and tau, 36 this is the first study to link a quadratic trajectory of brain activation with neurodegeneration, a recognized proxy of clinical severity 37,38 and time to dementia 5 …”
Section: Discussionmentioning
confidence: 99%
“…There has been growing interest in hyperactivation as an early signature of Alzheimer's disease (AD). This interest stems from the observation of higher task‐related functional magnetic resonance imaging (fMRI) activation in individuals with mild cognitive impairment (MCI) than in cognitively healthy controls (HC) 1–6 . This contrasts the observation of lower level of activation, or hypoactivation, in individuals with dementia or in the late stage of MCI 7–9 .…”
Section: Introductionmentioning
confidence: 99%